2015
DOI: 10.1297/cpe.24.51
|View full text |Cite
|
Sign up to set email alerts
|

Clinical spectrum and outcome of invasive filamentous fungal infections in children with Type 1 diabetes: North Indian experience

Abstract: There is scarcity of data on spectrum and outcome of invasive filamentous fungal infections (IFIs) in children with Type 1 diabetes (T1D) from developing countries. A retrospective review of medical records of children with T1D hospitalized with IFI over the past decade at the Pediatric Endocrinology and Diabetes Unit of a large tertiary care hospital of North India was performed with an aim to study their clinical spectrum, hospital course and final outcome. Of the 10 patients studied, nasal/paranasal involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 19 publications
2
12
0
Order By: Relevance
“…Our experience with invasive filamentous fungal infections in patients with T1D, predominantly caused by zygomycetes, is similar with the mean time from presentation to diagnosis of 5.8 ± 4.7 days (range 1-14 days) and debridement surgeries performed immediately after confirmation of diagnosis [5]. The relatively better outcome in our patients was probably a result of earlier diagnosis and treatment effected by a very dedicated team of pediatric endocrinologists, otolaryngologists, mycologists, histopathologists, intensivists, and pediatric surgeons at our center [4,5]. The overall survival rate of 55 % in the study by Kolekar, although at par with most centers in the world, could be related to the differences in the timings of diagnosis and surgery in their patients.…”
supporting
confidence: 65%
See 2 more Smart Citations
“…Our experience with invasive filamentous fungal infections in patients with T1D, predominantly caused by zygomycetes, is similar with the mean time from presentation to diagnosis of 5.8 ± 4.7 days (range 1-14 days) and debridement surgeries performed immediately after confirmation of diagnosis [5]. The relatively better outcome in our patients was probably a result of earlier diagnosis and treatment effected by a very dedicated team of pediatric endocrinologists, otolaryngologists, mycologists, histopathologists, intensivists, and pediatric surgeons at our center [4,5]. The overall survival rate of 55 % in the study by Kolekar, although at par with most centers in the world, could be related to the differences in the timings of diagnosis and surgery in their patients.…”
supporting
confidence: 65%
“…In our recent study on 4 children with Type 1 diabetes (T1D) and rhinosinus mucormycosis, the mean time to confirm the diagnosis was 3.5 days (range 1-7 days) and endoscopic or open surgery was performed within a week of hospitalization in all patients [4]. Our experience with invasive filamentous fungal infections in patients with T1D, predominantly caused by zygomycetes, is similar with the mean time from presentation to diagnosis of 5.8 ± 4.7 days (range 1-14 days) and debridement surgeries performed immediately after confirmation of diagnosis [5]. The relatively better outcome in our patients was probably a result of earlier diagnosis and treatment effected by a very dedicated team of pediatric endocrinologists, otolaryngologists, mycologists, histopathologists, intensivists, and pediatric surgeons at our center [4,5].…”
supporting
confidence: 51%
See 1 more Smart Citation
“…The most significant risk factors are: prolonged neutropenia, former broad-spectrum antibiotic therapy and diabetes including steroid-induced [4]. Review of the paediatric pulmonary mucormycosis reports published since 2010 based on PubMed and Cochrane databases showed that mucormycosis risk factors were: neutropenia (61.5% patients), broad-spectrum antibiotic therapy (35%), previous treatment with voriconazole (31%) and diabetes (27%) (Table 1) [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. A total of 26 patients were identified: 19 children suffered from haematological disease, 5 had diabetes, one had osteosarcoma and one was diagnosed after a neardrowning incident.…”
Section: Discussionmentioning
confidence: 99%
“…Children with poorly controlled diabetes have increase susceptibility to bacterial and fungal infection due to various alterations in their immune response such as decreased T-lymphocyte and neutrophil function, decreased inflammatory cytokine secretion, decreased complement system and anti-oxidant system responses, and probably decreased antibody response (6,7). There is no substantial reason to believe that the clinical course of children with poorly controlled diabetes and COVID-19 could be different from what has been observed in adult patients.…”
Section: Poor Metabolic Controlmentioning
confidence: 99%